Relation between traumatic experience and post-traumatic symptomatics in Lithuanian Afganistan war veterans with post-traumatic stress disorder - Domanskaitė-Gota, Vėjūnė; Gailienė, Danutė; Kazlauskas, Evaldas (Psichologija, 2009)
The aim of this paper is to assess what potential traumatic life-events and experiences are related to PTSD in the Lithuanian Afghanistan war veterans (N = 174). Data in this study were collected from a questionnaire survey with a sample of 268 Lithuanian men aged 32 to 52, who were on military duty (compulsory military service) in the Soviet army in 1979–1989. Four regions (capital cities, cities, small cities, and countryside), with the sample allocation proportionate to the distribution of Lithuanian population, geographically stratified the sample; 174 men served in Afghanistan during the Soviet Union – Afghanistan war. They were divided into two groups according to the manifestation of posttraumatic stress disorder. One group consists of 108 men without PTSD and 46 men with PTSD and sub-clinical level of PTSD (25 and 21 respectively). The following variables were investigated: demographics, traumatic life-events or conditions, PTSD and sub-clinical level of PTSD (Harvard Trauma Questionnaire, Mollica et al., 1992). The Lithuanian Afghanistan war veterans with PTSD and sub-clinical level of PTSD reported significantly more lifetime traumatic events and conditions. The average number of traumatic events per man with PTSD and sub-clinical level of PTSD was 12.4 and 10 for those without PTSD (F = 1.58, df =152, p < 0.05). The average number of direct exposure events per Lithuanian Afghanistan war veteran with PTSD and sub-clinical level of PTSD was 8 and 6 for veterans without PTSD (F = 10.2, df = 152, p < 0.002). There was a significant correlation between PTSD and the amount of direct exposure and particular traumatic experience: neglect in childhood, loss of a family member, mental illness in the family, absence of parents, violent assault, persecution, and struggle for existence. The Lithuanian Afghanistan war veterans with PTSD and without PTSD had a very similar experience of military operations and combats and the duration of their service didn’t differ. Afghanistan war veterans with PTSD and sub-clinical level of PTSD experienced more traumatic life-events and conditions than did veterans without PTSD, Veterans with PTSD and a sub-clinical level of PTSD, more often than veterans without PTSD, experienced traumatic exposure related to the family, violent assault and struggle for existence. Mental illness in the family, loss of a family member and violent assault were predictive of PTSD and sub-clinical level of PTSD in the Lithuanian Afghanistan war veterans.